The Effect of Study Program Accreditation on Decision-Making of New Students Through Promotion in Higher Education in Mojokerto - Rosanna Wulandari; Yudiyanto Tri Kurniawan; Siti Kori’ah; Anita Kusumaningrum; Ari Kartiko (STAI Hubbulwathan Duri, 2022)
The research was conducted at a university in Mojokerto Regency. The selection of this area is because Mojokerto district has a geographical location close to the city of Surabaya, the capital of the province of East Java and Malang, which we know as a student city in Indonesia. This study aims to analyze the accreditation of decision-making through promotion. The method used in this study uses a quantitative method with an explanatory research design, which means explaining the relationship of each variable in selecting the sample using probability sampling with a random sampling approach. The analytical tool used is to use a validity test and a reliability test where the instrument is declared valid if r count r table, while it is declared reliable if the Cronbach alpha value is 0.60. hypothesis testing using techniques analysis SEM (structural equation modelling) or AMOS (analysis of moment structure). The steps taken in the SEM analysis are by developing a model based on concepts and theories, construct-path chart, Conversion of a path diagram to a structural model, elect matrix input, Solution standard model, and goodness evaluation of fit index and Interpretation and modification. The results of hypothesis testing in this study indicate that the three hypotheses have a significant effect, and the promotion variable is able to mediate the study program accreditation variable on decision-making.